[LEGISLATIVE PROGRAM DETAIL C. MASSACHUSETTS] (Tufts Archival Research Center, 2007)
Marginalia; Incomplete; Outline of lobbying activities regarding Massachusetts public smoking legislation. Focuses on indoor air quality legislation standards and local restaurant ordinances. Summarizes issue, lists resources, and details steps of implementation. Itemizes expenditures. Discusses grass roots options.